Comparison of 2-year mortality according to obesity in stabilized patients with type 2 diabetes mellitus after acute myocardial infarction: results from the DIAMOND prospective cohort registry. Issue 1 (December 2015) - Won, Ki-Bum; Hur, Seung-Ho; Cho, Yun-Kyeong; Yoon, Hyuck-Jun; Nam, Chang-Wook; Kim, Kwon-Bae; Bae, Jang-Ho; Choi, Dong-Ju; Ahn, Young-Keun; Park, Jong-Seon; Kim, Hyo-Soo; Choi, Rak-Kyeong; et al.
Abstract Background After acute myocardial infarction (AMI), the replicated phenomenon of obesity paradox, i.e., obesity appearing to be associated with increased survival, has not been evaluated in stabilized (i.e., without clinical events within 1 month post AMI) Asian patients with diabetes mellitus (DM). Methods Among 1192 patients in the DIabetic Acute Myocardial InfarctiON Disease (DIAMOND) Korean multicenter registry between April 2010 and June 2012, 2-year cardiac and all-cause death were compared according to obesity (body mass index ≥25 kg/m2 ) in 1125 stabilized DM patients. Results Compared with non-obese DM patients (62 % of AMI patients), obese DM patients had: higher incidence of dyslipidemia (31 vs. 24 %, P < 0.01); lower incidence of chronic kidney disease (26 vs. 33 %) (P < 0.01); higher left ventricular ejection fraction after AMI (53 ± 11 vs. 50 ± 12 %, P < 0.001); and lower 2-year cardiac and all-cause death occurrence (0.7 vs. 3.6 % and 1.9 vs. 5.2 %, both P < 0.01) and cumulative incidence in Kaplan–Meier analysis (P < 0.005, respectively). Likewise, both univariate and multivariate Cox hazard regression analyses adjusted for the respective confounders showed that obesity was associated with decreased risk of both cardiac [HR, 0.18 (95 % CI 0.06–0.60), P = 0.005; and 0.24 (0.07–0.78), P = 0.018, respectively] and all-cause death [0.34 (0.16–0.73), P = 0.005; and 0.44 (0.20–0.95), P = 0.038]. Conclusions In a Korean population of stabilized DM patients after AMI, non-obese patients appear to have higher cardiac and all-cause mortality compared with obese patients after adjusting for confounding factors.